PENDAMPINGAN DENGAN PENDEKATAN KDEPE DALAM PENGEMBANGAN TAMAN TEMATIK LIANA DI KEBUN RAYA GIANYAR - I Nengah Suka Widana; I Gusti Ayu Rai; I Wayan Suanda; Ni Nyoman Parmithi; Putu Ryan Widyastaguna (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Since its soft opening on July 17 2017, the Gianyar Botanical Gardens has built several thematic parks, namely the upakara thematic park, liana thematic park, and other parks currently under construction. The liana thematic park is one of the thematic parks that is being developed based on the potential diversity of liana plant types that already exist in the KRG. The main problems addressed in mentoring activities in the development of liana thematic gardens are lack of access arrangements to liana thematic park, minimal collection of plant types, minimal information about liana thematic park, and lack of supporting hardscape facilities to increase liana thematic park capacity. Implementation of activities from 29 September to 1 October 2022, by applying the KDEPE approach (Coordination, Documentation, Evaluation, Common Perception and Execution). The results achieved are (a) entry access to the liana thematic park is more organized, making it easier for visitors; (b) there was an increase in the number of liana plant collections based on their types (initial 12 after assistance became 21 types). (c) There is information regarding collection of liana plants with scientific name labels and the writing of a book entitled Liana Botanical Gardens Gianyar.